Strengthening the Strategy in Achieving the Achievements of the Musabaqah Tilawatil Qur’an (MTQ) Caravan of Kerinci Regency at Jambi Provincial Level - Usman, Usman; Vitaloka, Wulansari; Usman, A’zhami Alim (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2025)
The achievements of the Kerinci Regency MTQ caravan at the provincial level had been degraded from 10 districts and cities. Kerinci occupies the last rank, namely 10 in 2023, and in 2024 it would rank 7th. This study explores how to develop strategies for achieving the achievements of the Musabaqah Tilawatil Qur’an (MTQ) caravan in the Kerinci district at the Jambi provincial level. This study used qualitative descriptive with semi-structured and unstructured data collection to explore data from participants by purposive sampling set by four people. The participant's names were created under a pseudonym to maintain their confidentiality. The results of the interviews were analyzed using the theories of data coding, theme identification, review, theme naming, and reporting. The results show the importance of an integrated strategy to improve the achievement of the Kerinci Regency Musabaqah Tilawatil Qur’an (MTQ) caravan at the Jambi Province level. The main steps include recruiting competent coaches, involving local and provincial coaches, and selecting potential participants to ensure the best quality. The coaching is carried out on an ongoing basis with a technical and mental approach, which local and provincial trainers coordinate. The coaching time is longer than six steps, with one wave lasting from five to 30 days and distributed within three months. Implementing a planned and directed strategy, Kerinci Regency has an excellent opportunity to improve the achievements of MTQ caravans sustainably at the provincial level to improve the achievements of MTQ caravans sustainably at the provincial level. Abstrak. Prestasi kafilah MTQ Kabupaten Kerinci di tingkat provinsi telah mengalami penurunan dari 10 kabupaten dan kota. Kerinci menempati peringkat terakhir, yaitu peringkat 10 pada tahun 2023, dan pada tahun 2024 mengalami perbaikan mendapatkan peringkat 7. Penelitian ini mengeksplorasi bagaimana mengembangkan strategi untuk mencapai prestasi kafilah Musabaqah Tilawatil Qur’an (MTQ) di Kabupaten Kerinci pada tingkat provinsi Jambi. Penelitian ini menggunakan metode deskriptif kualitatif dengan pengumpulan data semi-terstruktur dan tidak terstruktur untuk mengeksplorasi data dari peserta yang dipilih secara purposive sampling yang terdiri dari empat orang. Nama-nama peserta dibuat dengan menggunakan nama samaran untuk menjaga kerahasiaan mereka. Hasil wawancara dianalisis menggunakan teori pengkodean data, identifikasi tema, tinjauan, penamaan tema, dan pelaporan. Hasil penelitian menunjukkan pentingnya strategi terintegrasi untuk meningkatkan prestasi kafilah Musabaqah Tilawatil Qur’an (MTQ) Kabupaten Kerinci di tingkat Provinsi Jambi. Bagian pertama merekrut pelatih yang kompeten, melibatkan pelatih lokal dan provinsi, serta memilih peserta yang berpotensi untuk memastikan kualitas terbaik. Bagian kedua, pembinaan dilakukan secara berkelanjutan dengan pendekatan teknis dan mental, yang dikoordinasikan oleh pelatih lokal dan provinsi. Waktu pembinaan lebih dari enam gelombang, dengan satu gelombang berlangsung dari lima hingga 30 hari dan dibagi dalam tiga bulan. Dengan menerapkan strategi yang terencana dan terarah, Kabupaten Kerinci memiliki peluang yang baik untuk meningkatkan prestasi kafilah MTQ secara berkelanjutan di tingkat provinsi.